A praxeology of the value of life. A critique of Rothbard’s argument - Nowakowski, Paweł (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2024)
The present paper aims to study the issue of the value of life in Murray N. Rothbard’s work, and to examine his argument for the contention that “life should be an objective ultimate value” and that “the preservation and furtherance of one’s life takes on the stature of an incontestable axiom.” Rothbard’s assumptions and presuppositions are investigated and critically assessed. Using conceptual and logical analysis rooted mostly in the praxeological method of economics (as developed by Mises and Rothbard himself) and the theory of value (Scheffler, Raz, Elzenberg), it is demonstrated that Rothbard’s account is fallacious both on its own as well as on broader theoretical grounds. It is argued that what Rothbard could—under his specific assumptions about valuing—correctly claim is only that an actor values life to some extent, rather than that life has an objective ultimate value or preservation and furtherance of one’s life has an axiomatic status. The theoretical argument is supported by empirical illustration from suicide terrorism. The paper submits that Rothbard’s position on the value of life is unsound, and that using his argumentation as it stands cannot succeed.
Keywords: praxeology; time preference; Murray Newton Rothbard; valuing; value of life; libertarianism